PEMANFAATAN PEKARANGAN RUMAH UNTUK MEWUJUDKAN KELUARGA MANDIRI PANGAN (MAPAN) - Redi Hermanto; Satya Santika; Ike Natalliasari; Eva Mulyani (Jurnal Pengabdian Siliwangi, 2021)
The implementation of the Food Security Scheme Community Service program (PbM-KP) aims to: (1) motivate and educate the public about the importance of doing something useful in order to meet their food intake needs independently, (2) optimizing the yards around the house as a source fulfilling family food needs, (3) increasing the potential of the community through counseling and assistance activities in cultivating sources of food intake, which includes carbohydrate, protein and forage (KPH) intake, (4) realizing MaPan Families ( Independent Food). Based on these objectives, the targets and outputs of this activity are as follows: (1) direct provision of materials and tools in the form of plant seeds and planting media, and direct provision of materials and tools in the form of catfish seeds to be managed independently; (2) produce scientific publications published in ISSN National Journals, such as the Siliwangi Service Journal, and (3) publish the implementation of activities through mass media. The method to be used in this activity emphasizes the delivery of information / education to the community through outreach activities that are patterned and structured, mentoring and continuous evaluation. The conclusions of these activities are (1) Increasing people's knowledge about the importance of doing something useful in order to meet food intake needs independently; (2) This service activity provides education to residents on how to use the house yard to cultivate sorghum, vegetables and catfish in buckets, in order to meet their needs for carbohydrate, protein and forage intake; and (3) The members of the community are very enthusiastic about participating in every stage of this service activity.